HUMAN RESOURCES DEVELOPMENT IN THE IMPLEMENTATION OF SERVICE EXELLENCE AT THE LIBRARY AND ARCHIVES DEPARTEMENT OF SUKABUMI REGENCY - IRAWATI HANDAYANI; ERRY SUNARYA; DARMO H SUWIRYO (CV KULTURA DIGITAL MEDIA, 2021)
The research was motivated by the suspicion that the development of Human Resources in applying service excellence at Libraray and Archives Department of Sukabumi regency had not run optimally. Meanwhile, the research was aimed at determining: (1) the strategy of Human Resources development in implementing service excellence at Libraray and Archives Department of Sukabumi regency, (2) Obstacles encountered in developing Human Resources in implementing service excellence at Libraray and Archives Department of Sukabumi regency, and (3) efforts to overcome the obstacles in the develoment of human resources in implementing service excellence at Libraray and Archives Department of Sukabumi regency. The reserach applied qualitative approach. The informants of the research were Head of Sub-section of Personnel and General Affairs, Head of Archives Processing Division, Head of Promotion and Development of Reading Culture Section, Head of Human Resources Development Section, Archivists, and Librarians. The results of the research are (1) Human Resource Development at the Archives and Library Department of Sukabumi Regency is carried out through the implementation of a proportional transfer, promotion, training and performance appraisal system, (2) There are internal and external obstacles in developing human resources at the Archives and Library Department of Sukabumi Regency, and (3) There have been efforts made to overcome both internal and external obstacles in developing human resources at the Archives and Library Department of Sukabumi Regency. Based on the results of the research, the management of the Archives and Library Department of Sukabumi Regency is advised to: (1) Improve the competency of archival and library human resources through formal, non-formal, and informal education related to their work field, (2) Structural officials are to be more technically understanding about procedures and techniques for processing archives and library as this can help carry out the smooth running of official activities, and (3) develop and maintain the consistency of existing facilities and infrastructure in compliance with standardization so that they can better support archival and library human resources in performing official activities.